AI will take your job, and it's for the best : embracing the new social contract for the age of AI - Schatten, Jeff; Aires, Teresa (Emerald Publishing Limited, 2025)
AI Will Take Your Job, and It's for the Best is a bold and timely exploration of how artificial intelligence is reshaping the future of work--and why this transformation is something to embrace rather than fear. In a world where automation is rapidly replacing human tasks, this book offers a fresh, optimistic perspective. It explores how AI, far from being a job-stealing threat, presents humanity with the opportunity to redefine the meaning of work and purpose. Jeff Schatten and Theresa Aires dive deep into the economics, sociology, and psychology behind this shift, introducing the AI Growth and Redistribution Impact Doctrine (AI-GRID). This framework lays out a set of guiding principles and policy recommendations to ensure that AI's benefits are distributed equitably, offering a practical roadmap for policymakers, business leaders, and individuals alike. AI Will Take Your Job, and It's for the Best examines how AI will free people from mundane tasks, allowing them to pursue more meaningful and creative roles. From the rise of the human-AI hybrid workforce to discussions on Universal Basic Income, Schatten and Aires provide a vision of a future where AI and humanity coexist for mutual benefit and offer an insightful and thought-provoking look at the opportunities ahead. It's more than a forecast--it's a guide to thriving in the age of AI and embracing the radical new social contract it requires.